Heat stress assessment system based on guideline on heat stress management - Rahwani Raihan, Abdul Wahab (2019)
Heat stress related-illnesses can occur and may result in death where is can cause loss of focus and physical performance. In fact, mental performance for worker who is working in a hot environment will degrades in advance. Proper management of heat stress according to the established Guideline on Heat Stress Management at Workplace 2016 is to guide employers in to recognize, estimate, prevent and treat heat stress at workplace where to avoiding discomfort from hot environment at work. It is believed that most of the industries already recognized the guideline, but unavailability of effective technique had delay the implementation of this requirement. This research study is conducted to introduce a systematic technique of heat stress assessment in industries to achieve a safe working environment and without risk to the organization. At the same time to prevent the presence of heat related-illness. This study covered analysis of element requirements for heat stress assessment based on Guideline on Heat Stress Management at Workplace 2016, development of framework and database assessment system as well as concept validation through case study from real data of a manufacturing industry. Implementation of this technique will help employer to control the presence of heat stress related-illness among the worker.